Twenty-Four Hour Blood Pressure Response to Empagliflozin and Its Determinants in Normotensive Non-diabetic Subjects - Zanchi, Anne; Pruijm, Menno; Muller, Marie-Eve; Ghajarzadeh-Wurzner, Arlène; Maillard, Marc; Dufour, Nathalie; Bonny, Olivier; Wuerzner, Grégoire; Burnier, Michel (Frontiers in Cardiovascular Medicine, 2022)
Background: Sodium–glucose co-transport 2 inhibitors (SGLT2i) lower blood pressure (BP) in normotensive subjects and in hypertensive and normotensive diabetic and non-diabetic patients. However, the mechanisms of these BP changes are not fully understood. Therefore, we examined the clinical and biochemical determinants of the BP response to empagliflozin based on 24-hour ambulatory BP monitoring. Methods: In this post-hoc analysis of a double-blind, randomized, placebo-controlled study examining the renal effects of empagliflozin 10 mg versus placebo in untreated normotensive non-diabetic subjects, the one-month changes in 24h ambulatory BP were analyzed in 39 subjects (13 placebo/26 empagliflozin) in regard to changes in biochemical and hormonal parameters. Results: At one month, empagliflozin 10mg decreased 24-hour systolic (SBP) and diastolic (DBP) BP significantly by -5±7 mmHg (p<0.001) and -2±6 mmHg (p=0.03). The effect on SBP and DBP was more pronounced during nighttime (resp. -6±11 mmHg, p=0.004; -4±7 mmHg, p=0.007). The main determinants of daytime and nighttime SBP and DBP responses were baseline BP levels (for daytime SBP: coefficient -0.5; adj. R2: 0.36; p=0.0007; for night-time SBP: coefficient -0.6; adj. R2: 0.33; p=0.001). Although empaglifozin induced significant biochemical changes, none correlated with blood pressure changes including urinary sodium, lithium, glucose and urate excretion and free water clearance. Plasma renin activity and plasma aldosterone levels increased significantly at one month suggesting plasma volume contraction, while plasma metanephrine and copeptin levels remained the same. Renal resistive indexes did not change with empagliflozin. Conclusions: SGLT2 inhibition lowers daytime and nighttime ambulatory systolic and diastolic BP in normotensive non-diabetic subjects. Twenty-four jour changes are pronounced and comparable to those described in diabetic or hypertensive subjects. Baseline ambulatory BP was the only identified determinant of systolic and diastolic BP response. This suggests that still other factors than sustained glycosuria or proximal sodium excretion may contribute to the resetting to lower blood pressure levels with SGLT2 inhibition.